A fully coupled method for massively parallel simulation of hydraulically driven fractures in 3‐dimensions. (18th September 2016) - Settgast, Randolph R.; Fu, Pengcheng; Walsh, Stuart D.C.; White, Joshua A.; Annavarapu, Chandrasekhar; Ryerson, Frederick J.
Summary: This paper describes a fully coupled finite element/finite volume approach for simulating field‐scale hydraulically driven fractures in three dimensions, using massively parallel computing platforms. The proposed method is capable of capturing realistic representations of local heterogeneities, layering and natural fracture networks in a reservoir. A detailed description of the numerical implementation is provided, along with numerical studies comparing the model with both analytical solutions and experimental results. The results demonstrate the effectiveness of the proposed method for modeling large‐scale problems involving hydraulically driven fractures in three dimensions. © 2016 The Authors. International Journal for Numerical and Analytical Methods in Geomechanics published by John Wiley & Sons Ltd.